2018
DOI: 10.1039/c8fo00349a
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarumZDY04 exhibits a strain-specific property of lowering TMAOviathe modulation of gut microbiota in mice

Abstract: Trimethylamine N-oxide (TMAO), which is oxidized from trimethylamine (TMA) by hepatic flavin-containing monooxygenases (FMOs), promotes the development of atherosclerosis and is a new target for the prevention and treatment of cardiovascular disease from the perspective of intestinal flora. TMA is transformed by intestinal flora from TMA-containing nutrients, such as choline. Some small molecular agents lower serum TMAO and/or cecal TMA levels. However, probiotics that can effectively reduce serum TMAO levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 37 publications
1
72
1
3
Order By: Relevance
“…The bacterium Lactobacillus plantarum which is found in fermented vegetable foods and milk products reduced circulating cholesterol and triglycerides in hypercholesterolemic mice [154]. L. plantarum also decreased TMAO levels in mice and could inhibit TMAO-induced atherosclerosis [155]. Similar results were found upon administration of L. rhamnosis to ApoE-deficient mice on a high-fat diet.…”
Section: Administration Of Single Strains and Microbiota Replacementsupporting
confidence: 60%
“…The bacterium Lactobacillus plantarum which is found in fermented vegetable foods and milk products reduced circulating cholesterol and triglycerides in hypercholesterolemic mice [154]. L. plantarum also decreased TMAO levels in mice and could inhibit TMAO-induced atherosclerosis [155]. Similar results were found upon administration of L. rhamnosis to ApoE-deficient mice on a high-fat diet.…”
Section: Administration Of Single Strains and Microbiota Replacementsupporting
confidence: 60%
“…Probiotic treatment has been shown to reduce levels of TMAO in correlation with decreased atherosclerosis development; however, this effect is strain specific. A recent study investigated potential TMAO‐lowering property of five different probiotic strains . Only Lactobacillus plantarum ZDY04 was able to significantly reduce plasma TMAO, and it was suggested that this effect was achieved via remodeling of the gut microbiota .…”
Section: Probiotics and Tmaomentioning
confidence: 99%
“…ApoE −/− mice [47,48] L. plantarum ZDY04 Reduced TMAO-induced lesion development; decreased plasma TMAO ApoE −/− mice [49] L. acidophilus and B. bifidum Reduced TC, HDL-C, and LDL-C Human [50] VSL#3 Reduced TC, LDL-C, TG, hsCRP; increased HDL-C and improved insulin sensitivity Human [51] S. thermophiles, L. bulgaricus, L. acidophilus LA5, B. lactis BB12…”
Section: Probiotics and Lesion Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prebiotics are nondigestible dietary ingredients that can be fermented by specific intestinal microflora to stimulate the growth of beneficial bacteria colonized in the gut. Probiotics are live and natural microbiota that can be administrated safely (). Both prebiotics and probiotics are good candidates for the modulating the gut microbiota and conferring favorable effects to the host.…”
Section: Inhibitors Of Enzymes In Tmao Formationmentioning
confidence: 99%